Analisis Penggunaan Bahan Bakar Palm Caul, Bark, dan Palm Sheel pada Sistem Boiler Multi Bahan Bakar di PT. Toba Pulp Lestari, Tbk Porsea - Marpaung, Juanda Herlambang; Tarigan, Nurlianna (CV. IRA PUBLISHING, 2023)
This research aims to calculate the amount of fuel in the multi-fuel boiler unit at PT Toba Pulp Lestari, Tbk. A boiler is a closed steam boiler, and the heat of combustion is transmitted to the water until it becomes hot steaming water or steam. In the work process, it is necessary to calculate the total fired and moisture to determine the efficient level of maturity for each unit. In this research, the author found that the energy needed to evaporate water in fuel up to 0% was Palm Caul 2303.67 kcal/kg, Palm Shell 3833.25 kcal/kg, and Bark 1513.69 kcal/kg. The energy used in the Multi Fuel Boiler requires Palm Caul 186,688.4 kg/hour, Palm sheel 97,683.6 kg/hour, and Bark 181,508.9 kg/hour.